Technology-mediated communication and ego identity. [article]. - Abregana, Betty C.
The present study is an attempt to view the concept of identity in the context of the global changes going in a world of technology. An Ego Identity Scale(Tan, et. al., 1977) was administered together with a questionnaire on technology-mediated communication to 322 Psychology students. The results showed that texting and electronic mail are perceived by identity achieved individuals as aids in maintaining relationships, but not as aids in creating relationships nor in self-disclosure. Also, those who were low on ego identity levels (i.,e.., identity diffused individuals) usually reacted in anger when they did not receive text messages from acquaintances. These and other findings serve to highlight the role that technology mediated communication plays in the search for identity.